The Evaluasi Penggunaan Obat Kemoterapi Pada Pasien Kanker Ovarium Di RSUP Fatmawati Periode September 2024. - Raden, Ditaa (Jurnal Farmasi Klinik Best Practice, 2025)
Ovarian cancer is a major malignancy in the female reproductive system. Treatment for this cancer can involve surgical procedures or the use of chemotherapy drugs, either orally or intravenously. This study was conducted to evaluate the use of chemotherapy drugs in ovarian cancer patients at RSUP Fatmawati. Data collection was carried out through a retrospective observation by gathering information on drug usage from the patients' medical records, which included data from 31 patients receiving treatment at RSUP Fatmawati in September 2024. Based on the obtained data, it was found that the most commonly used chemotherapy drug for cancer patients at RSUP Fatmawati is TAC (Paclitaxel + Carboplatin), accounting for 80.65%. Additionally, based on the chemotherapy regimens used at RSUP Fatmawati, the recovery percentage from several regimens ranged from 54.90% to 131.93%.